A dual-round signal amplification strategy for colorimetric/photoacoustic/fluorescence triple read-out detection of prostate specific antigen. Issue 36 (2nd April 2020) - Jiang, Chao; Huang, Yan; He, Ting; Huang, Peng; Lin, Jing
Abstract : A colorimetric/fluorescence/photoacoustic triple read-out detection of prostate specific antigen (PSA) was developed by using a silica coated Au@Ag core–shell nanorod (denoted Au@Ag@SiO2 ) based enzyme-linked immunosorbent assay (ELISA) system. Abstract : The detection of prostate specific antigen (PSA) is extremely important for the early diagnosis of prostate cancer. Herein, we report a dual-round signal amplification strategy for colorimetric/fluorescence/photoacoustic triple read-out detection of PSA using a silica coated Au@Ag core–shell nanorod (denoted Au@Ag@SiO2 ) based enzyme-linked immunosorbent assay (ELISA) system. In the presence of PSA, monoclonal primary antihuman PSA antibody (Ab1) captured PSA and was subsequently recognized by the secondary antihuman PSA detection antibody (Ab2) which was conjugated with glucose oxidase (GOx) functionalized magnetic beads (MBs) for signal amplification, then GOx catalyses the addition of glucose to generate hydrogen peroxide that etches the silver layer in Au@Ag@SiO2, thus producing abundant Ag + to realize the second signal amplification. With the degradation of the silver layer, an obvious color change (green-to-pink) of the Au@Ag@SiO2 solution could be observed by the naked eye and its surface plasmon resonance (SPR) absorption had a red-shift, enhancing photoacoustic signal read-out at 780 nm. Additionally, the released Ag + was caught by a Ag + -fluorescent probe (Ag + -FP) for enhanced fluorescence signal read-out. These results suggested that this ELISA system achieves a triple read-out detection of PSA. This work provides a promising strategy for multiple read-out detection of biomarkers, which has great potential in clinical diagnosis.